Oxidative Stress and Semen Quality Among Night- and Day-Shift Workers: A Cross-Sectional Study - Luca Boeri; Federica Passarelli; Ludovico Maria Basadonna; Edoardo Sorba; Giorgio Graps; Fabio Ciamarra; Damiano Dagnino; Valentina Parolin; Marco Nizzardo; Gianpaolo Lucignani; Emanuele Montanari (Antioxidants, 2025)
Introduction: Infertility affects 15% of couples, with oxidative stress recognized as a key contributor to male infertility. Night-shift work, through circadian disruption, may exacerbate oxidative imbalance and impair reproductive function. This study investigates the impact of night-shift work on oxidative stress and semen quality and evaluates the potential benefits of antioxidant supplementation in this context. Materials and Methods: We retrospectively analysed 96 white-European men aged 18–45, seeking fertility assessment at a single academic centre. Participants were classified as day or night workers based on their shift schedule, and all underwent standardised clinical, hormonal, and semen evaluations. Oxidative stress was assessed using the d-ROMs test. A subgroup of 40 patients (20 per group) treated for 3 months with antioxidant supplementation (Drolessano) to evaluate changes in oxidative stress and semen parameters was also considered. Statistical comparisons were performed using non-parametric tests and logistic regression analyses. Results: Night-shift workers exhibit significantly higher oxidative stress levels compared to day workers (median D-ROMs values of 340 vs. 280 U.CARR, p = 0.01), and a greater proportion of men exceeding the oxidative stress threshold (74.4% vs. 24.4%, p = 0.01). Logistic regression confirmed night-shift work as an independent predictor of elevated oxidative stress (OR 2.1, p = 0.001), even after adjusting for age and smoking. Following three months of antioxidant supplementation with Drolessano, both groups experienced significant reductions in oxidative stress (all p < 0.01), but night workers showed a substantially greater decrease (mean change −58.5 vs. −15.4 U.CARR, p = 0.001). Improvements in semen quality, including sperm concentration, motility, and morphology, were also more pronounced in the night group after treatment. Conclusions: At baseline, night-shift workers had significantly higher oxidative stress than day workers, likely due to circadian disruption. Both groups improved after antioxidant treatment, but night workers showed a greater reduction in D-ROMs. This pilot study might suggest a potential benefit of antioxidant therapy particularly in night workers.